The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/jcm9082613
|View full text |Cite
|
Sign up to set email alerts
|

Same-Day Versus Non-Simultaneous Extracorporeal Membrane Oxygenation Support for In-Hospital Cardiac Arrest Complicating Acute Myocardial Infarction

Abstract: Background: Although extracorporeal membrane oxygenation (ECMO) is used for hemodynamic support for in-hospital cardiac arrest (IHCA) complicating acute myocardial infarction (AMI), there are limited data on the outcomes stratified by the timing of initiation of this strategy. Methods: Adult (>18 years) AMI admissions with IHCA were identified using the National Inpatient Sample (2000–2017) and the timing of ECMO with relation to IHCA was identified. Same-day vs. non-simultaneous ECMO support for IHCA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…The U.S. studies showed differing trends in relationships for SES and outcomes according to age but not article quality (Data Supplement, http://links.lww.com/CCM/H327 and Supplemental Table 7, http://links.lww.com/CCM/H327). Of six adult ECMO studies investigating mortality, five observed patients (83%) with higher SES measured by ZIP code median income or Medicare wage index had improved survival (88, 103, 122–124). Three showed no association with other outcomes (complications or readmissions) (56, 65, 125, 126).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The U.S. studies showed differing trends in relationships for SES and outcomes according to age but not article quality (Data Supplement, http://links.lww.com/CCM/H327 and Supplemental Table 7, http://links.lww.com/CCM/H327). Of six adult ECMO studies investigating mortality, five observed patients (83%) with higher SES measured by ZIP code median income or Medicare wage index had improved survival (88, 103, 122–124). Three showed no association with other outcomes (complications or readmissions) (56, 65, 125, 126).…”
Section: Resultsmentioning
confidence: 99%
“…The 24 payer studies were from the United States. Eight studies reported improved survival in patients with private relative to government insurance (28, 77, 88, 89, 106, 123, 128, 129). Eight found no survival difference (55, 65, 81, 92, 130–133), with variable cost, complication, readmission, and LOS results (31, 33, 56, 70, 125, 126, 128, 134), including one with higher renal replacement in privately insured patients (83).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 Demographic characteristics including age, sex, race/ethnicity, hospital characteristics, acute organ failure, mechanical circulatory support, cardiac procedures, fibrinolytic use, tracheostomy, percutaneous endoscopic gastrostomy, and other noncardiac organ support use were identified for all admissions using previously used methodologies from our group (Table S1 ). 21 , 22 , 23 , 37 For the purposes of this analysis, race/ethnicity was classified as White, Black, and others (Hispanic, Asian or Pacific Islander, Native American, Others). Coding for race in NIS combines “race” and “ethnicity” provided by the data source into 1 data element (RACE).…”
Section: Methodsmentioning
confidence: 99%